Nivolumab resistance in head and neck squamous cell carcinoma patients and future perspectives - Buchajska, Karolina; Mydlak, Anna; Zwoliński, Jakub; Wojtaszczyk, Kinga; Spławski, Bartosz (Contemporary Oncology/Współczesna Onkologia, 2025)
Head and neck cancer (HNC) cases are increasing globally, with resistance to immunotherapies such as nivolumab posing a significant challenge. This systematic review examines the mechanisms of nivolumab resistance in HNC, with a focus on intrinsic tumor factors, the immunosuppressive tumor microenvironment (TME), and immune checkpoint dysregulation. Intrinsic mechanisms, such as mutations that impair antigen presentation and MYC amplification, reshape the TME to promote immune evasion. The tumor microenvironment, enriched with immunosuppressive cells such as tumor-associated macrophages and myeloid-derived suppressor cells, further compromises nivolumab’s effectiveness. Moreover, cancer cells exploit immune checkpoints, including programmed death-ligand 1 (PD-L1), T-cell immunoglobulin and mucin domain-3, and LAG-3, to evade immune surveillance. Identifying predictive biomarkers, such as MYC amplification and PD-L1 expression, is essential for developing personalized treatments. This review underscores the complex nature of nivolumab resistance and the urgent need for comprehensive therapeutic strategies to improve outcomes in HNC patients.